(untitled) (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
This study aims to examine the effect of enforcement regulations, organizational ethical culture, organizatioal commitment to the tendency of fraud based on fraud triangle theory in Yogyakarta City Goverment . The data used is primary. Multiple regression analysis is the analytical method used. The sampling technique used in this study was the purpose sampling method and obtained 83 data samples. The regression test results show that organizational commitment negatively affect the tendency of fraud in the public sector. Whereas enforcement regulations, organizational ethical culture have on effect the tendency of fraud.